Macro- and microenvironmental factors affecting tyre-breeding flies (Insecta: Diptera) in urbanised areas - Rubio, Alejandra (2013)
1. Urbanisation is often considered a main driver of changes in the structure of insect communities. To assess macro- and microenvironmental factors determining the occurrence and community structure of fly larvae in water-filled artificial containers, a total of 13 848 individuals were collected among 1380 water- filled tyres inspected along an urbanisation gradient in temperate Argentina. 2. According to the best generalized linear mixed model obtained for fly occurrence, the probability of finding an occupied tyre was greater in large tyres with high water volume, containing organic matter and located in shaded conditions under high vegetation cover in backyards. Regarding macroenvironmental factors, fly occurrence decreased as the urbanisation level increased. 3. The anova revealed a negative effect of urbanisation on all variables used to characterize the fly community structure. The number of occupied tyres, the relative abundance of individuals, the species richness, and the Shannon diversity index showed consistent patterns with significantly lower values at high urbanisation level. 4. Community composition also varied along the urbanisation gradient, revealing three major groups of fly species: those found exclusively in highly urbanised areas, those found in the less urbanised sites, and those collected across the entire gradient.